2001
DOI: 10.1177/108835760101600407
|View full text |Cite
|
Sign up to set email alerts
|

Application of Choice-Making Intervention for a Student with Multiply Maintained Problem Behavior

Abstract: A functional behavioral assessment was completed for a 10-year-old boy with autism and problem behavior. The assessment indicated that both teacher attention and escape from task demands maintained his problem behavior. A choice-making intervention that involved allowing the participant to choose between completing work alone and subsequently receiving a break with teacher attention versus working with teacher assistance was implemented. Initial data collected on the intervention suggested that choice making d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…According to the researchers, without instruction in choice making, children with ID/DD are at risk for having their preferences ignored and their protests misinterpreted as informed consent, lack of interest or even contentment. Not having choices is a problem by itself; however, research has also shown a significant correlation between lack of choice and negative behaviors, including aggression, noncompliance, temper tantrums, and running away (Peterson, Caniglia, & Royster, 2001;Umbreit & Blair, 1996). These same investigators also found that providing choices decreased unwanted behaviors and resulted in positive behavioral outcomes.…”
Section: Supporting Instruction Of Self-determination Skillsmentioning
confidence: 99%
“…According to the researchers, without instruction in choice making, children with ID/DD are at risk for having their preferences ignored and their protests misinterpreted as informed consent, lack of interest or even contentment. Not having choices is a problem by itself; however, research has also shown a significant correlation between lack of choice and negative behaviors, including aggression, noncompliance, temper tantrums, and running away (Peterson, Caniglia, & Royster, 2001;Umbreit & Blair, 1996). These same investigators also found that providing choices decreased unwanted behaviors and resulted in positive behavioral outcomes.…”
Section: Supporting Instruction Of Self-determination Skillsmentioning
confidence: 99%
“…Most function-based interventions include (a) providing teacher attention (e.g., praise and points; Kamps, Wendland, & Culpepper, 2006); (b) self-monitoring (Kamps et al); (c) teaching social skills (e.g., asking for help; Kamps et al); (d) reducing task duration and breaking down task steps (Moore, Anderson, & Kumar, 2005); (e) receiving breaks and working with adults or peers (Peterson, Caniglia, & Royster, 2001); and (f) interspersing instruction between preferred activities (Blair, Liaupsin, Umbreit, & Kweon, 2006). More intensive tertiary supports are described in another article in this issue (Eber, Breen, Rose, Unizycki, & London, 2008).…”
Section: Typical Featuresmentioning
confidence: 99%
“…Four studies evaluated choicemaking (Cosden, Gannon, & Haring, 1995;Dyer, Dunlap, & Winterling, 1990;Powell & Nelson, 1997;Romaniuk et al, 2002). Studies that were considered primarily investigations of functional assessment (e.g., Cooper et al, 1992;Dunlap, Foster-Johnson, Clarke, Kern, & Childs, 1995;Dunlap et al, 1993;Peterson, Caniglia, & Royster, 2001) were also excluded. Studies that were considered primarily investigations of functional assessment (e.g., Cooper et al, 1992;Dunlap, Foster-Johnson, Clarke, Kern, & Childs, 1995;Dunlap et al, 1993;Peterson, Caniglia, & Royster, 2001) were also excluded.…”
Section: Reviewed Studiesmentioning
confidence: 99%